DIAGNÓSTICO DE LA RELACIÓN MAESTRO ALUMNO EN LA ESCUELA (Fiep Bulletin - online, 2013)
The objective was to study and diagnose the student teacher ratio in primary school Boy Heroes of Chapultepec, 54 students included 31 girls and 23 boys of primary school, his two masterpieces. To conduct the study tools used qualitative research methodologies, exploratory, based on the hermeneutic phenomenological observation and conservative. To obtain the results, the content analysis: three attitudes were investigated, basic trust in the class authenticity, relationship of person-to-person, empathic understanding. Same that were excellent in 1 ° A in the relationship teacher referred to by the master trust student ratio q in an atmosphere of warmth, no empathy. As regards the group of 4 ° A, the relationship was good, with less intensity was presented empathic understanding and trust. My study's conclusions were that there are three attitudes in the groups only with greater intensity in the 1 ° A, the diagnostic is yes there is a relationship between teacher and student.
Keywords: Teacher; student; empathy; trust; relationship